2019
DOI: 10.1371/journal.pone.0218488
|View full text |Cite
|
Sign up to set email alerts
|

Extracurricular activity profiles and wellbeing in middle childhood: A population-level study

Abstract: This study examined profiles of participation in extracurricular activities (ECAs) in 4 th grade children ( N = 27,121; Mean age = 9.20 years; SD = .54; 51% male) in British Columbia, Canada. Latent class analyses were used to establish activity profiles and determine class membership; ANCOVA was used to investigate differences in mental wellbeing (optimism, life satisfaction, self-concept) and perceived overall health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 52 publications
3
31
0
2
Order By: Relevance
“…It is particularly interesting to discuss this in light of the large variation in PA found among the children who participated in the study. A recent study on extracurricular activity among Canadian fourth graders also showed great variations in the children's activity levels, revealing that the children who engaged in PA and sport activities together with others scored higher on measurements related to well-being and health than non-active children [64]. Intervention studies in American ASPs indicate that structured after-school PA programing might increase the children's activity levels [65].…”
Section: Plos Onementioning
confidence: 98%
“…It is particularly interesting to discuss this in light of the large variation in PA found among the children who participated in the study. A recent study on extracurricular activity among Canadian fourth graders also showed great variations in the children's activity levels, revealing that the children who engaged in PA and sport activities together with others scored higher on measurements related to well-being and health than non-active children [64]. Intervention studies in American ASPs indicate that structured after-school PA programing might increase the children's activity levels [65].…”
Section: Plos Onementioning
confidence: 98%
“…To address the question of whether children's development is linked to different patterns of afterschool settings as suggested by bio-ecological theory (Bronfenbrenner & Morris, 2006), person-centered analyses are needed. Several investigators (Metzger et al, 2009, Morris & Kalil, 2006Oberle et al, 2019;Zarrett et al, 2009) have used pattern-centered analytic techniques to study children and youth who experience different combinations of afterschool settings, which were then related to child developmental outcomes. In a study of low-income, ethnically diverse early adolescent, middle-school students, Metzger et al (2009) used cluster analyses to identify six profiles of extracurricular activities, which were differentially associated with academic achievement, problem behavior, and adult support.…”
mentioning
confidence: 99%
“…Regarding the non-participation in any extracurricular activity, we found that students at secondary education were those who attended fewer activities. In previous studies, higher values of non-participation were reported [18,19], with over 30% of students not participating in extracurricular activities. In our study, different and significant values were found according to the educational level, although these differences were not greater than 30%.…”
Section: Discussionmentioning
confidence: 77%